2017
DOI: 10.1061/(asce)em.1943-7889.0001043
|View full text |Cite
|
Sign up to set email alerts
|

Basic Mechanical Properties of Wet Granular Materials: A DEM Study

Abstract: International audienceNumerical simulations, by the discrete element method (DEM), of a model granular assembly, made of spherical balls, are used to investigate the influence of a small amount of an interstitial wetting liquid, forming capillary bridges between adjacent particles, on two basic aspects of granular material rheology: (1) the plastic response in isotropic compression, and (2) the critical state under monotonic shear strain, and its generalization to steady, inertial flow. Tensile strength F0=πΓa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…The model of capillary bridge. We assume that the liquid inside the agglomerate is in the 'pendular' state with a uniform distribution of capillary bridges between particles 38,[53][54][55][56][57][58][59] . This distribution may be a consequence of mixing the liquid with the particles, drainage of a saturated packing, or capillary condensation from a vapor.…”
Section: Methodsmentioning
confidence: 99%
“…The model of capillary bridge. We assume that the liquid inside the agglomerate is in the 'pendular' state with a uniform distribution of capillary bridges between particles 38,[53][54][55][56][57][58][59] . This distribution may be a consequence of mixing the liquid with the particles, drainage of a saturated packing, or capillary condensation from a vapor.…”
Section: Methodsmentioning
confidence: 99%
“…For P * << 1, initial loose structures are stabilized by adhesion and the relevant force scale is F 0 . For large reduced pressures P * >> 1, externally imposed forces dominate the adhesive strength, the relevant force scale is Pa 2 [9]. The main objective of the present paper is the study of the effect of a gradual compression, starting from cohesion-dominated loose states at small P * , and ending in confinement-dominated denser states at large P * .…”
Section: Compaction Processmentioning
confidence: 99%
“…In this study, the results are priorly shown in the conventional compression -decompression curves in soil mechanics e-log(P * ), in which e = 1/ -1. Three regimes can be classified in the compression curve, depending on the range of the pressure P * [9]. A first regime, thereafter called regime I, is observed in the range of low reduced pressures P * .…”
Section: Effect Of Initial Solid Fractionmentioning
confidence: 99%
See 2 more Smart Citations